1988
DOI: 10.1002/j.1460-2075.1988.tb03079.x
|View full text |Cite
|
Sign up to set email alerts
|

Human lysosomal acid phosphatase is transported as a transmembrane protein to lysosomes in transfected baby hamster kidney cells.

Abstract: BHK cells transfected with human lysosomal acid phosphatase (LAP) cDNA (CT29) expressed 70‐fold higher enzyme activities of acid phosphatase than non‐transfected BHK cells. The CT29‐LAP was synthesized in BHK cells as a heterogeneously glycosylated precursor that was tightly membrane associated. Transfer to the trans‐Golgi was associated with a small increase in size (approximately 7 kd) and partial processing of the oligosaccharides to complex type structures. CT29‐LAP was transferred into lysosomes as shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 28 publications
2
52
0
1
Order By: Relevance
“…A sequence ladder (lanes 3 -6) was used as size markers. Nucleotidc, nt exon 11 is cleaved by proteolytic processing in the lysosomes, where the transmembrane form is converted to the soluble mature form of LAP [3]. The exact site for processing has not yet been determined, The proteolytic processing involves two cleavages; the first by a cysteine proteinase within the cytoplasmic tail and the second by an aspartyl proteinase within the luminal domain close to the site, where LAP exits from the membrane (S. Gottschalk and A. Waheed, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sequence ladder (lanes 3 -6) was used as size markers. Nucleotidc, nt exon 11 is cleaved by proteolytic processing in the lysosomes, where the transmembrane form is converted to the soluble mature form of LAP [3]. The exact site for processing has not yet been determined, The proteolytic processing involves two cleavages; the first by a cysteine proteinase within the cytoplasmic tail and the second by an aspartyl proteinase within the luminal domain close to the site, where LAP exits from the membrane (S. Gottschalk and A. Waheed, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…The deduced sequence and the expression of the cDNA revealed that LAP is synthesized as a transmembrane protein with a cleavable signal sequence at the N-terminus and a short cytoplasmic tail of 18 amino acids. The membrane-bound precursor is transported independently of mannose 6-phosphate receptors to the lysosomes, where the soluble mature form of LAP is generated by proteolytic processing [3]. LAP shares with other lysosomal membrane glycoproteins the dense glycosylation of the luminal domain, a short cytoplasmic domain, mannose-6-phosphate-receptor-independent targeting and partial localization at the cell surface [4-61. While the primary structure of several lysosomal membrane glycoproteins is known, their functions, expression and gene structures remain to be elucidated.…”
mentioning
confidence: 99%
“…For instance, AcPh is soluble in Giardia but exists as a type-I membrane protein containing a YXXØ-type internalization sequence in cells as different as Leishmania and humans (Gottlieb and Dwyer, 1981;Waheed et al, 1988;Shakarian et al, 2002), with transport to the lysosome occurring through several cycles of plasma membrane internalization and recycling. In the lysosome of mammalian cells, the luminal domain of AcPh is processed and released in soluble form (Peters et al, 1990).…”
Section: Lysosomal Proteinsmentioning
confidence: 99%
“…Oligonucleotide-directed mutagenesis of the codon for [9,10]. In pSVL constructs the inserted DNA was under the control of the SV40 late promoter; in pBHE constructs it was under that of the SV40 early promoter.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%
“…BHK cells were grown for 2-3 weeks in the presence of 5 ,ug of puromycin/ml followed by isolation of stably-transfected clones. Microinjection of cRNA in oocytes P29 cDNA inserted into the EcoRI site of pGEM (Promega Biotec) was transcribed using SP6 polymerase and purified as described [10]. RNA (25 ng) in 50 nl of water was injected into Xenopus laevis oocytes (stage V) as described [11].…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%